An In-Depth Examination of the Sociocultural Framework-Informed Practical Model of Scaffolded Feedback in Enhancing Senior High School English Writing Instruction - Xu, Shuyu (International Journal of Social Sciences and Public Administration, 2024)
This study deeply analyzes the application of scaffolded feedback in senior high school English writing instruction under the framework of sociocultural theory. Based on Vygotsky’s Zone of Proximal Development (ZPD) concept and Lantof’s 13-level Regulatory scale, this paper constructs a scaffolded feedback model to improve students’ writing ability through personalized instruction. This paper argues that under the framework of this model, teachers should follow the principles of negotiation, graduation and contingency when providing scaffolded feedback to ensure that students gradually transition from dependence on external adjustment to self-adjustment. In conclusion, the research finds that scaffolded feedback model can effectively promote the development of students’ self-correction ability and stimulate their independent learning and critical thinking. And the research can also provide theoretical basis and practical guidance for English writing teaching in high school.